Establishing log reduction values for wastewater treatment processes from ambient influent and effluent pathogen monitoring data - Tchobanoglous, George; Kenny, John; Leverenz, Harold; Oliveri, Adam (Frontiers in Environmental Science, 2022)
In developing wastewater treatment regulations and guidelines for potable reuse, the reduction of pathogens is of critical importance. In draft regulations, the state of California has proposed overall treatment process log reduction values (LRVs) of 20, 14, and 15 respectively for viruses, Giardia cysts, and Cryptosporidium oocysts, for direct potable reuse. In meeting the log reduction requirements, agencies have sought to obtain credit for LRVs achieved consistently through secondary biological and tertiary wastewater treatment, in addition to the LRVs achieved through advanced water treatment. The purpose of this paper is to illustrate how to determine pathogen LRVs, using ambient wastewater treatment pathogen monitoring data and the rank-paired covariant method of analysis.